2020
DOI: 10.1108/bij-09-2020-0492
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the dimensions of servicescape using mixed method approach – A study of beauty salons

Abstract: PurposeThe purpose of this study aims to explore the dimensions assessing the servicescape of beauty salons and provides suggestions to improve the salon's servicescape.Design/methodology/approachA mixed-method design is used in the sequence of thematic analysis through focus group technique followed by exploratory factor analysis and confirmatory factor analysis were used to assess the beauty salon's servicescape.FindingsThe exploration of factors in beauty salons is determined with three dimensions: the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…The greater proportion of young respondents in the sample is attributed to research findings which have shown that younger people prefer using technology-enabled services (Rojas-Mendez et al ., 2017). In addition, it has been suggested in the literature that the average age of Indians is generally expected to be around 29 years (Kampani and Jhamb, 2021). The demographic details of the respondents have been provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The greater proportion of young respondents in the sample is attributed to research findings which have shown that younger people prefer using technology-enabled services (Rojas-Mendez et al ., 2017). In addition, it has been suggested in the literature that the average age of Indians is generally expected to be around 29 years (Kampani and Jhamb, 2021). The demographic details of the respondents have been provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…An employee-oriented culture reflects its organisational value system in terms of rewards and providing a comfortable environment. As per organisational role theory, the workplace environment affects employees physically and emotionally (Wanous and Reichers, 2000;Kampani and Jhamb, 2020). If a firm understands the employee's journey from their point of view, they are much successful in delivering desired customer experiences.…”
Section: Employee Orientationmentioning
confidence: 99%
“…Moreover, a female's physical appearance attains high attention not merely in traditionally enriched cultural societies but also in western societies (Morris et al, 2018). Moreover, the northwest region of India is well known for its ostentatious lifestyle and higher spending capacity among its population (Jhamb et al, 2021; Kampani & Jhamb, 2021), while a dramatic increase in organised retailing has changed consumer attitudes and consumption patterns in the region (Jain & Mishra, 2018).…”
Section: Methodsmentioning
confidence: 99%